2003
DOI: 10.1037/0735-7036.117.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and developmental consequences of early rearing experience for captive giant pandas (Ailuropoda melanoleuca).

Abstract: Mother-reared (MR) and peer-reared (PR) captive giant panda (Ailuropoda melanoleuca) cubs were compared to evaluate the effects of early removal from mother on behavioral development. Males and females and twins and singletons were compared to assess the effects of social setting on behavioral development. Subjects included 2 PR females, 3 MR females, 3 MR males, and 3 mothers. MR cubs spent more time manipulating bamboo and fell more often than PR cubs. PR cubs spent more time inactive. Male cubs directed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In addition, both small RNA-seq and stem-loop qRT-PCR results indicated that the abundance of exogenous bamboo miRNAs changed with the increasing greenness of giant panda milk (Fig. 5D,E), which may be highly associated with the stress fasting of the giant panda within the first three days after delivery 57 . This result emphasizes the potential oral intake of exogenous plant miRNAs from food sources in the giant panda.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, both small RNA-seq and stem-loop qRT-PCR results indicated that the abundance of exogenous bamboo miRNAs changed with the increasing greenness of giant panda milk (Fig. 5D,E), which may be highly associated with the stress fasting of the giant panda within the first three days after delivery 57 . This result emphasizes the potential oral intake of exogenous plant miRNAs from food sources in the giant panda.…”
Section: Resultsmentioning
confidence: 95%
“…Early rearing socialization and maternal-offspring interaction plays an important role in the development of giant pandas [Snyder et al, 2003[Snyder et al, , 2006Swaisgood et al, 2003]. Cubs in the wild remain with their mothers for 1.5-2.5 years [Lu et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…Cubs in the wild remain with their mothers for 1.5-2.5 years [Lu et al, 1994]. In captivity, cubs that are allowed to remain with their mother past the age of 6 months are more active and spend a significantly greater amount of time manipulating bamboo than those raised by peers [Snyder et al, 2003]. Further studies on the ontogeny of the wadding behavior in the giant panda would be useful in determining the extent to which this behavior is affected by early socialization.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is difficult to identify pregnancy in giant pandas based on changes in progesterone levels (5). At present, research on captive giant pandas has focused on the detection of estrus and mating (6,7), as well as infant care and development (2,8). However, there are sparse reports on the physiological changes of pregnant pandas.…”
Section: Introductionmentioning
confidence: 99%